Stempellinella Brundin, 1947 (Diptera: Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species - Orel, Oksana V. (Zootaxa, 2023)
Two new species of the genus Stempellinella Brundin, 1947, S. bazovae sp. nov. and S. chirka sp. nov., from Eastern Siberia and the Russian Far East are described. Illustrated redescriptions of males for further three species, S. coronata Inoue, Kawai et Imabayashi, 2004, S. edwardsi Spies et Saether, 2004, S. tamaseptima (Sasa, 1980) are given. Stempellinella ministylus Ree, 2015 is a new synonym Stempellinella coronata Inoue, Kawai et Imabayashi, 2004. Key to the males and pupae of the Russian Far East and Eastern Siberia Stempellinella species is provided.